The effectiveness of soft and semi-rigid cervical collars on acute cervical radiculopathy - Kasapoğlu Aksoy, Meliha; Altan, Lale; Güner, Altuğ (The European Research Journal, 2018)
Objectives. Cervical radiculopathy is one of the common causes of the neck pain. Medical devices in the form of cervical collars are frequently recommended in acute cervical radiculopathy. We aim to investigate and compare the effect of soft and semi-rigid cervical collars on neck pain, disability and daily life activities in the patients with acute cervical radiculopathy. Methods. We designed a prospective, single-blind, randomized controlled study. This study was conducted on 101 patients who were diagnosed with clinical features of radiculopathy and imaging showing cervical disc herniation. Visual Analog Scale (VAS), Neck Disability Index (NDI) and SF-36 were applied to the subjects. Evaluation of the patients was done before the treatment and 2 weeks and 6 weeks after the start of the treatment. Patients were divided into three groups according to the computer-generated randomization table: Soft cervical collar, semi-rigid cervical collar and control group. The patients in collar groups were asked to wear the collars for 8 hours during the day for the first 2 weeks.Results. Comparison of the soft cervical collar group with the control group showed significantly better improvement in the former in VAS and NDI scores at week 2 and 6 (p < 0.05), in SF-36 pain perception subunit at week 2 (p < 0.05), and in SF-36 physical component score at week 6 (p < 0.05). Comparison of the semi-rigid cervical collar group with the control showed significantly better improvement in the former for NDI scores and SF-36 pain perception subunit at week 2 and 6 (p < 0.05). Conclusions. The results of our study have indicated that the use of soft and semi-rigid cervical collars was more effective than conservative treatment in treatment of neck pain and disability in acute cervical radiculopathy in the short term. Soft cervical collars were also found to be more effective for pain management than semi-rigid cervical collars.